Firm value in crisis: Effects of firm-level transparency and country-level institutions - Enikolopov, Ruben; Petrova, Maria; Stepanov, Sergey (Journal of Banking & Finance, 2014)
Recent empirical research suggests that country-level and firm-level governance institutions are substitutes with respect to their effect on firm value. In this paper we demonstrate that during a crisis these institutions may actually become complements. Specifically, we find that the decline in companies’ valuation during the financial crisis of 2007–2009 was more sensitive to firm-level transparency in countries with stronger investor protection. We propose a theoretical model that reconciles our findings with the results in the literature. In our model, during “normal times” strong firm-level governance is crucial to attract outside financing in countries with weak investor protection, but is less important in countries with good investor protection. During a crisis, however, investment opportunities decline even in countries with strong investor protection, and, as a result, relative importance of firm-level governance increases in such places.